Indoor radon risk assessment in education buildings from kindergarten to high school in Campania region - Fabrizio Ambrosino; Fabrizio Ambrosino; Giuseppe La Verde; Giuseppe La Verde; Roberta Oliva; Mohamed Y. Hanfi; Antonio Sarno; Mariagabriella Pugliese; Mariagabriella Pugliese (Frontiers in Built Environment)
In the context of the 2024 Italian National Radon Action Plan requiring the monitoring of workplaces, work activities, and buildings with public access, 222Rn activity concentrations in 67 schools in the Campania region (Italy) —kindergartens, primary schools, secondary schools and high schools—were measured using passive detectors over a year. The information collected for evaluation involved the construction materials used, the covering of walls and floors, the intended use of the rooms, and the type of people exposed, whether students, teachers, or administrative staff. Annual effective dose (AED), lung cancer cases (LCC), and excess lifetime cancer risk (ELCR) for these three people categories were estimated. The average 222Rn activity concentration was 262 Bq/m3 in kindergartens (std. dev. = 158 Bq/m3), 292 Bq/m3 for both primary and secondary schools (std. dev. = 189 Bq/m3 and 213 Bq/m3, respectively), and 150 Bq/m3 (std. dev. = 205 Bq/m3) in high schools. The difference between schools built of tuff and those of concrete was statistically different, with average activity of 276 Bq/m3 vs. 144 Bq/m3. As expected, the floor level had a considerable impact, with the activity concentration reducing as the distance from the ground floor increased. The average AED ranged between 2.2 mSv (kindergarten) and 1.1 mSv (high school) for students and between 1.3 mSv and 0.6 mSv for teachers. AED for administrative staff was estimated to be 2.5 mSv on average. The highest AED corresponded to the highest LCC and ELCR for administrative staff, estimated at 45 per million people and 8.6%, respectively. Such a proposed approach could be used to implement a risk management system in accordance with the principles of radiation protection and prevention of harm to human health.